Early treatment improves urodynamic prognosis in neurogenic voiding dysfunction: 20 years of experience - Lucia M. Costa Monteiro; Glaura O. Cruz; Juliana M. Fontes; Eliane T.R.C. Vieira; Eloá N. Santos; Grace F. Araújo; Eloane G. Ramos (Brazilian Society of Pediatrics, 2017)
Objective: To evaluate the association between early treatment and urodynamic improvement in pediatric and adolescent patients with neurogenic bladder. Methodology: Retrospective longitudinal and observational study (between 1990 and 2013) including patients with neurogenic bladder and myelomeningocele treated based on urodynamic results. The authors evaluated the urodynamic follow‐up (bladder compliance and maximum bladder capacity and pressure) considering the first urodynamic improvement in two years as the outcome variable and early referral as the exposure variable, using a descriptive and multivariate analysis with logistic regression model. Results: Among 230 patients included, 52% had an early referral. The majority were diagnosed as overactive bladder with high bladder pressure (≥40 cm H2O) and low bladder compliance (3 mL/cmH2O) and were treated with oxybutynin and intermittent catheterization. Urodynamic follow‐up results showed 68% of improvement at the second urodynamic examination decreasing bladder pressure and increasing bladder capacity and compliance. The percentage of incontinence and urinary tract infections decreased over treatment. Early referral (one‐year old or less) increased by 3.5 the probability of urodynamic improvement in two years (95% CI: 1.81-6.77). Conclusion: Treatment onset within the first year of life improves urodynamic prognosis in patients with neurogenic bladder and triplicates the probability of urodynamic improvement in two years. The role of neonatologists and pediatricians in early referral is extremely important.